Factors determining stakeholders' perception of kenaf cultivation in Kelantan, Malaysia - Amir Mustafa, Amira Mas Ayu (2014)
Global warming has led to renewed interest in the more sustainable use of natural fibers in composite materials. This has led to a resurgence of interest on Kenaf fibers. The Malaysian government has selected Kenaf as a new commodity and natural fiber to be given support and priority. Even though the Government has provided incentives and support in Kenaf development, the progress in Kenaf cultivation has not met the expectation of the Government. The objectives of this study are i) to identify the important stakeholders, their stakes and roles in Kenaf cultivation in Kelantan and ii) to determine the critical factors influencing farmers' participation in Kenaf cultivation. For the first objective, social network analysis has been used to identify the stakeholders in Kenaf cultivation and for the second objective based from the result in the first objective, factor analysis is applied to map out the stakeholder' perspective in Kenaf cultivation. Data for social network analysis and factor analysis are collected through interviews using structured questionnaire. This paper provides the preliminary findings of this investigation. The result from social network analysis enables the identification of the real critical stakeholder in Kenaf cultivation which is the farmer. This key stakeholder is the target for fostering the growth of the Kenaf industry. The fmdings from factor analysis show that there are six significant factors; i) economic potentials in Kenaf cultivation, ii) strategies of tobacco cultivation, iii) grievances over Kenaf cultivation, iv) farmers' perspectives in changing crop cultivation, v) challenges on market assurances, and (vi) campaign and promotion to attract farmers involvement in Kenaf cultivation.